ANALISIS USAHATANI CABAI RAWIT DI KECAMATAN SUNGAI RUMBAI KABUPATEN MUKOMUKO - Prasetio Budi; Novitri Kurniati; Edy Marwan (Jurnal AGRIBIS, 2020)
This research was done in Sungai Rumbai District, Mukomuko regency, and was conducted in March to April 2019. The study aims to determine the income of cayyene pepper farming, efficieny, feasibilitu study, and production BEP as well as sales BEP in the farmimg in Sungai Rumbai District, Mukomuko Regency. The location of this study was intentionally determined in Sungai Rumbai District, Mukomuko Regency on the consideration that Sungai Rumbai subdistrict is a center of cayyene pepper plantation in Mukomuko regency. Respondents that were involved in this study were 34 cayyene pepper farmers in Sungai Rumbai district of Mukomuko Regency. The data taken were both primary and secondary data. The primary data was directly taken from the farmers by means of interviews, and thr secondary data was taken from related institutians. The results of the analysis of study show that the average income of cayyene pepper farmer was Rp. 13.772.382,36 per planting season. Then the efficiency of R/C Ratio was 2,64 and the feasibility of B/C Ratio was 1,64. The BEP production was 334,65 kg, and sales BEP was Rp. 8.366.352,94 per one production period ( 6 Months). Key Word : income, efficieny, feasibility study, and production BEP as well as sales BEP.